KONFLIK LAHAN KAMPUNG TUA TANJUNG UMA KECAMATAN LUBUK BAJA KOTA BATAM PROVINSI KEPULAUAN RIAU TAHUN 2004-2016 - Wan Khairina Malinda; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Kampung Tua Tanjung Uma is an old village in Batam City. Land conflict occur in Kampung Tua Tanjung Uma, between the Kampung Tua Tanjung Uma’s society, Badan Pengusahaan Batam (BP Batam), and the third party. The purpose of this research is to knows first, how Kampung Tua’s land management, second, the causes of land conflict in Kampung Tua Tanjung Uma, and third, actors who have a role in handling Kampung Tua Tanjung Uma land conflicts and how is the role of those actors.The kind of this research is descriptive qualitatuve research methods. Location of this research conducted in Kampung Tua Tanjung Uma Kecamatan Lubuk Baja Kota Batam Provinsi Kepulauan Riau. The thecniques of data collection is done by interview and documentation. While data analysis done by analyzing results of interview and documentation.The result of this research and study about Konflik Lahan Kampung Tua Tanjung Uma Kecamatan Lubuk Baja Kota Batam Provinsi Kepulauan Riau Tahun 2004-2016, can be concluded that Kampung Tua’s land management in Batam City is ruled by Badan Pengusahaan Batam (BP Batam) because Keppres Nomor 41 Tahun 1973 is still valid. The cause of land conflicts is because legality of Kampung Tua land is unclear and the process of determination the land area not being agreed between Kampung Tua Tanjung Uma’s society, Badan Pengusahaan Batam (BP Batam), and Pemerintah Kota Batam. Actors who take a role in handling conflicts are Pemerintah Kota Batam, Dewan Perwakilan Rakyat Daerah Kota Batam, Lembaga Adat Melayu Kota Batam, and Rukun Khazanah Warisan Batam. The role conducted done by mediator and facilitator, and Rukun Khazanah Warisan Batam also take a role to accomodate Kampung Tua’s society in Batam City.Keywords: Conflicts, Land Conflicts, Kampung Tua Tanjung Uma